ANALYSIS OF FACTORS AFFECTING THE DEMAND FOR KEROSENE IN URBAN HOUSEHOLDS IN INDONESIA - Neila Soraya; Bambang Eko Afiatno (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The government has been converting kerosene to gas since 2007. However, households that use kerosene for cooking purposes are still found in urban areas in Indonesia, even though access to gas is already very easy. This study aims to investigate the factors that influence the demand for kerosene in urban households in Indonesia. Based on the March 2018 Susenas data from BPS, it was found that 15,143 urban households still use kerosene, 80.20 percent of them use kerosene as the main fuel for cooking. Using multiple linear regression, it was found that the price of kerosene and the gender of the head of the household had a negative effect on the intensity of kerosene use in urban households. Meanwhile, income per capita, age of the head of the household, number of household members, and education level of the head of household have a positive effect on the intensity of kerosene use in urban households.